Technology and an Organization’s Business Model - Gordon, Lawrence A. (Transactions on Engineering and Computing Sciences, 2024)
The contemporary view of the interconnected digital world began to take shape in the mid-1990s with the commercialization of the Internet.[1] In the early years of the 21st Century, social media companies started to surface.[2] The use of computers and the Internet, combined with social media, have substantially changed the way most companies conduct business when compared to the way business was conducted prior the mid-1990s. The effective execution of this changed business model is based on digital interconnections among computer-based communication systems.